Subsidy Reforms and Poverty Alleviation - Bhambhri, Chandra (IMF Working Papers; Working Paper ;, 2001)
This paper presents a general framework for characterizing the optimal pattern of subsidies for poverty alleviation under budgetary constraints and suggests possible reforms for the existing pattern of subsidies. The government may subsidize or tax goods in order to meet its objectives. The paper introduces the concept of a consumer equilibrium and shows that there are cases of equilibria in which reforms can generate not only fiscal savings but also Pareto improve the welfare of both poor and wealthy consumers.